Towards an imaginative Learning in the teaching of Arabic as a foreign language - BADAOUI, Mahmoud (Journal of Human Sciences, 2020)
The aim of this article is to suggest how teachers of Arabic as a foreign language might create, through an imaginative and entertaining learning, the use of unusual, funny, mysterious and ambiguous resources, highly inspiring and evocative, a warm and fresh atmosphere where the learner, interacting with humanistic activities speaking to his emotions and childhood remembrances, exciting his curiosity … dreams, plays with music, conveys odd, strange, unexpected, crazy … ideas to amaze his classmates and make them laugh, getting rid of that serious and gloomy traditional language classroom!